Thomas Bailey Aldrich papers - Aldrich, Thomas Bailey, 1836-1907.
Outgoing correspondence of Aldrich and his wife addressed primarily to Edward Howard House relating to personal matters. Also includes a volume containing a holograph and typescript copy of "Monody on the Death of Wendell Phillips."
Author and editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: House, Edward Howard, -- 1836-1901 -- Correspondence; Phillips, Wendell, -- 1811-1884.; Authors; Editors